The Urban Worlds of Latin and Anglo America: PrefatoryThoughts - Morse, Richard (Urban History Review / Revue d'histoire urbaine, 1980)
This introductory paper examines some of the main questions raised by the papers presented to the urbanization symposium in Vancouver. Comparisons between the Latin American urban experience and that of the United States and Canada revealed basic contrasts in spite of some broad hemispheric similarities. Differences were particularly apparent in the residual influence of native society on later European settlement, in the role of the state versus private commerce in growth and development, and in the differing class structures.